Timing-specific Debridement, Antibiotics, and Implant Retention and 2-Stage Revision for Megaprosthesis-Related Infection: Optimizing the Window Period for Improved Outcomes - Rajeev K. Sharma, MS, DNB, Mch; Imelda Lumban-Gaol, MD; Udit Vinayak, MS, DNB; Nicolaas C. Budhiparama, MD, PhD (Arthroplasty Today, 2025)
Background: This study aimed to evaluate the outcomes of debridement, antibiotics, and implant retention (DAIR) procedures and 2-stage revision surgeries in patients with periprosthetic joint infection following megaprosthesis, including treatment failure; the patient-reported outcomes; and to determine the survival rates of the revised megaprosthesis. Methods: A retrospective study of 30 patients diagnosed with periprosthetic joint infection following megaprosthesis between 2018 and 2023, with minimum 1-year follow-up. Patients with previous unsuccessful debridement in other institutions were excluded. Patients presenting within 4 weeks of megaprosthesis implantation underwent the DAIR procedure, while those presenting after this window were taken for a 2-stage revision surgery. The primary outcome was treatment failure, defined as persistent wound complication or the need for subsequent surgical intervention. The secondary outcomes included patient-reported outcomes, assessed with the Oxford Hip Score and Oxford Knee Score, and the survival rates of the revised megaprosthesis. Results: The mean follow-up duration for all patients was 38 ± 12.6 months. Improvement was found for Oxford Hip Score and Oxford Knee Score with mean 34.22 ± 9.2 and 32.40 ± 8.1, respectively, at the 1-year follow-up. DAIR achieved an 81% success rate (13 out of 16) and 2-stage exchange had a 71.4% success rate (10 out of 14). Conclusions: Both DAIR and 2-stage exchange procedures yielded favorable functional outcomes with satisfactory 2-year survival function. Careful patient selection and indication management are crucial for optimal results. Level of evidence: Level IV.